Edukasi UMKM melalui Mozaik Indonesia RRI Tarakan: UMKM Bertahan di Era Marketplace dalam Genggaman - Andri Yogi Adyatma Prasetyo; Syaddam (Politeknik Negeri Samarinda, 2025)
Over the years, MSMEs have traditionally marketed their products in physical markets. However, as technology and the Internet have advanced, consumer behavior has shifted towards digital markets. This shift has presented new challenges for MSMEs in a highly competitive market. To address this, a community service initiative has been launched in the form of a radio talkshow. This community service activity is carried out in the form of a talk show on the radio, using the interview method on the talk show on the radio, Lecturers from the Politeknik Bisnis Kaltara share knowledge, experience, and practical strategies that can help MSMEs in expand market reach, increasing operational efficiency, and facing various challenges that arise in the increasingly competitive and dynamic digital market environment. Community service activities in the form of a talk show on the radio are an important educational tool for Lecturers at the Politeknik Bisnis Kaltara to disseminate knowledge and provide valuable insights to MSMEs operating in the digital market facing competition in the digital market.